Multi-principal-element alloy coating with multistage heterostructure based on co-reaction nitridation mechanism and preparation method of multi-principal-element alloy coating
Through the multi-level heterostructure multi-principal alloy coating based on the co-reaction nitriding mechanism, the problem of synergistic improvement of wear resistance and mechanical properties of multi-principal alloys is solved, and significant strength, toughness, hardness and tribology are achieved. Performance improvements.
Patent Information
- Application Number
- CN202411459981.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
Existing multi-main alloys have difficulties in synergistic improvement of wear resistance and mechanical properties.
A multi-level heterostructure multi-principal alloy coating based on the co-reactive nitridation mechanism is used to form a gradient multi-principal alloy coating through a high-energy beam cladding process of CoCrNiX multi-principal alloy powder and CoCrNiZY multi-principal alloy powder. , and generate multi-principal nitrides through ion nitriding treatment.
It significantly improves the strength, toughness, surface hardness and tribological properties of the composite coating, and synergistically improves the overall mechanical properties of the material.
Smart Images

Figure CN119307909A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface engineering, and relates to a multi-principal-element alloy coating with a multi-level heterogeneous structure based on a co-reaction nitridation mechanism and a preparation method thereof. Background Art
[0002] Surface wear of components is a common problem in advanced manufacturing, which not only threatens the operational safety and stability of equipment, but also brings additional maintenance time and economic burden. In recent years, multi-principal alloys have attracted extensive attention in the field of materials science due to their unique four core effects. At the same time, plasma nitriding, as a mature surface hardening process, has been widely proven to significantly improve the performance of materials. Therefore, domestic and foreign scholars have introduced traditional ion nitriding technology into the strengthening of HEAs (high entropy alloys).
[0003] Due to the multi-subject characteristics of HEAs, excellent performance and unique strengthening mechanism can be obtained after nitriding. These effects work together to give HEAs excellent physical and chemical properties, including high wear resistance, high strength, excellent corrosion resistance and excellent high temperature stability. Therefore, scholars at home and abroad have introduced traditional ion nitriding technology into the strengthening of HEAs. For example, Jiangsu University of Technology proposed "a high entropy alloy gradient composite material based on in-situ reaction and its preparation method", which nitrided the surface of FeAlCrCoNi high entropy alloy with an equiatomic ratio, and obtained a gradient composite layer containing AlN particles by in-situ reaction on the surface of the high entropy alloy. The tensile strength and hardness of the coating were improved, but the improvement was not large. Meng et al. studied the nitrided layer of FeNiMnAlCrHEA and found that a large number of AlN particles were formed on the surface of FeNiMnAlCr HEA, and the hardness of the AlN-containing area was high. However, current research focuses on single-phase multi-principal alloys or blocky multi-principal alloys.
[0004] There are still few reports on the nitriding of multi-phase and multi-principal component alloys. Therefore, there is still great potential for improving the friction properties of multi-principal component alloys. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that it is difficult to synergistically improve the wear resistance and mechanical properties of existing multi-principal component alloys, and proposes a multi-principal component alloy coating with a multi-level heterogeneous structure based on a co-reaction nitridation mechanism and a preparation method thereof.
[0006] The multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitriding mechanism of the present invention consists of a CoCrNiX multi-principal alloy tough bottom layer, a CoCrNiZY multi-principal alloy top layer and a CoCrNiZY nitrided layer. The CoCrNiX multi-principal alloy powder is used as the cladding powder, and a high-energy beam cladding process is adopted to form a CoCrNiX multi-principal alloy tough bottom layer on the surface of a base material. Then, the CoCrNiZY multi-principal alloy powder is used as the cladding powder, and a high-energy beam cladding process is adopted to form a CoCrNiZY multi-principal alloy top layer on the CoCrNiX multi-principal alloy tough bottom layer. Finally, ion nitriding treatment is performed to form a CoCrNiZY nitrided layer.
[0007] Among them, X in the CoCrNiX multi-principal alloy powder represents Fe or Cu, Z in the CoCrNiZY multi-principal alloy powder represents Fe or Cu, and Y represents Ti, W, Ta, Nb, Mo, Zr or Hf.
[0008] The Y element in the CoCrNiZY multi-principal alloy of the present invention is an alloy element that is easy to nitrided and can promote the formation of Laves or BCC phases. The ion nitriding treatment is based on the unique thermodynamic and crystallographic properties of high entropy alloys, and the high degree of disorder and its multi-principal elements jointly participate in forming a complex nitrided layer during the ion nitriding process.
[0009] Based on the multi-principal component characteristics of the multi-principal component alloy, the present invention uses an ion nitriding process to co-react and generate multi-principal component nitrides on a gradient multi-principal component alloy coating. The multi-phase heterogeneous structure and gradient heterogeneous structure of the multi-principal component alloy form a multi-level heterogeneous structure, which synergistically improves the strength and toughness of the composite coating while greatly improving the surface hardness and tribological properties of the coating.
[0010] The preparation method of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism of the present invention is achieved by the following steps:
[0011] 1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material;
[0012] 2. Prepare CoCrNiX multi-principal alloy powder and CoCrNiZY multi-principal alloy powder respectively;
[0013] a. The preparation method of the CoCrNiX multi-principal alloy powder is as follows:
[0014] The four metal powders of Co, Cr, Ni and X are placed in a ball mill for ball milling and mixing according to the atomic ratio of Co:Cr:Ni:X=1:1:1:m, and then dried to obtain CoCrNiX multi-principal alloy powder;
[0015] b. The preparation method of the CoCrNiZY multi-principal alloy powder is as follows:
[0016] According to the atomic ratio of Co:Cr:Ni:Z:Y=1:1:1:m:n, five kinds of metal powders, Co, Cr, Ni, Z and Y, are placed in a ball mill for ball milling and mixing, and after drying, CoCrNiZY multi-principal alloy powder is obtained;
[0017] 3. Using CoCrNiX multi-principal alloy powder as cladding powder, the CoCrNiX multi-principal alloy powder is fed synchronously, and a high-energy beam cladding process is used to form a CoCrNiX multi-principal alloy toughness bottom layer on the surface of the pretreated substrate material;
[0018] 4. CoCrNiZY multi-principal alloy powder is used as cladding powder. The CoCrNiZY multi-principal alloy powder uses a synchronous powder feeding method and adopts a high-energy beam cladding process to form a CoCrNiZY multi-principal alloy top layer on the CoCrNiX multi-principal alloy toughness bottom layer to obtain a base material with a gradient multi-principal alloy coating;
[0019] 5. The top surface of the CoCrNiZY multi-principal alloy is then ground, polished and cleaned in sequence to obtain a base material with a gradient multi-principal alloy coating;
[0020] 6. Put the substrate material with the gradient multi-principal alloy coating into the cathode disk of the ion nitriding furnace, introduce NH3, and control the nitriding temperature to 500-600°C for ion nitriding treatment, so that the Co, Cr, Ni, Z, and Y elements react with the N element to generate multi-principal nitrides and then form a CoCrNiZY nitriding layer, thereby obtaining a multi-principal alloy coating with a multi-level heterogeneous structure;
[0021] In the CoCrNiX multi-principal alloy, X represents Fe or Cu, in the CoCrNiZY multi-principal alloy, Z represents Fe or Cu, Y represents W, Ta, Nb, Mo, Zr or Hf, m is 0.5 to 1.5, and n is 0.5 to 1.5.
[0022] The multi-principal alloy coating with a multi-level heterogeneous structure of the present invention successfully prepares a gradient multi-principal alloy coating formed by the gradual change of the content of FCC phase and hard phase (Laves phase or BCC phase) on the surface of CoCrNiX multi-principal alloy coating by precisely controlling the element migration process and recrystallization mechanism in the molten pool. This process benefits from the entropy change effect during recrystallization between elements and the unique mechanism of phase change caused by lattice distortion, so that the constructed gradient coating exhibits bonding performance that exceeds traditional metallurgical bonding methods. Furthermore, the co-reaction nitridation mechanism of the multi-principal alloy is used to in-situ generate NbN, AlN, CrN, Co 5.47N and other multi-component nitride gradient coatings, the distribution characteristics of the multi-component nitride particles in the gradient coating are characterized by a volume fraction and a gradual layout along the thickness direction. This unique design significantly enhances the bonding strength between the composite layer and the matrix material. The present invention cleverly combines the original high strength and good plasticity advantages of the multi-principal alloy, and forms a multi-level heterogeneous structure through the multi-phase structure, gradient multi-principal structure, and nitride gradient distribution of the multi-principal alloy, which greatly improves the overall mechanical properties of the material, especially in terms of surface hardness and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic diagram of a multi-principal alloy coating with a multi-level heterogeneous structure based on a co-reaction nitridation mechanism obtained in an embodiment;
[0024] Figure 2 X-ray diffraction diagrams of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism obtained in the example and the comparative example;
[0025] Figure 3 The top microstructure of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism obtained in the embodiment;
[0026] Figure 4 This is a comparison chart of the tribological properties of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism obtained in the example and the comparative example. DETAILED DESCRIPTION
[0027] Specific implementation method 1: The preparation method of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism of this implementation method is implemented according to the following steps:
[0028] 1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material;
[0029] 2. Prepare CoCrNiX multi-principal alloy powder and CoCrNiZY multi-principal alloy powder respectively;
[0030] a. The preparation method of the CoCrNiX multi-principal alloy powder is as follows:
[0031] The four metal powders of Co, Cr, Ni and X are placed in a ball mill for ball milling and mixing according to the atomic ratio of Co:Cr:Ni:X=1:1:1:m, and then dried to obtain CoCrNiX multi-principal alloy powder;
[0032] b. The preparation method of the CoCrNiZY multi-principal alloy powder is as follows:
[0033] According to the atomic ratio of Co:Cr:Ni:Z:Y=1:1:1:m:n, five kinds of metal powders, Co, Cr, Ni, Z and Y, are placed in a ball mill for ball milling and mixing, and after drying, CoCrNiZY multi-principal alloy powder is obtained;
[0034] 3. Using CoCrNiX multi-principal alloy powder as cladding powder, the CoCrNiX multi-principal alloy powder is fed synchronously, and a high-energy beam cladding process is used to form a CoCrNiX multi-principal alloy toughness bottom layer on the surface of the pretreated substrate material;
[0035] 4. CoCrNiZY multi-principal alloy powder is used as cladding powder. The CoCrNiZY multi-principal alloy powder uses a synchronous powder feeding method and adopts a high-energy beam cladding process to form a CoCrNiZY multi-principal alloy top layer on the CoCrNiX multi-principal alloy toughness bottom layer to obtain a base material with a gradient multi-principal alloy coating;
[0036] 5. The top surface of the CoCrNiZY multi-principal alloy is then ground, polished and cleaned in sequence to obtain a base material with a gradient multi-principal alloy coating;
[0037] 6. Put the substrate material with the gradient multi-principal alloy coating into the cathode disk of the ion nitriding furnace, introduce NH3, and control the nitriding temperature to 500-600°C for ion nitriding treatment, so that the Co, Cr, Ni, Z, and Y elements react with the N element to generate multi-principal nitrides and then form a CoCrNiZY nitriding layer, thereby obtaining a multi-principal alloy coating with a multi-level heterogeneous structure;
[0038] In the CoCrNiX multi-principal alloy, X represents Fe or Cu, in the CoCrNiZY multi-principal alloy, Z represents Fe or Cu, Y represents W, Ta, Nb, Mo, Zr or Hf, m is 0.5 to 1.5, and n is 0.5 to 1.5.
[0039] The X element in the CoCrNiX multi-principal alloy of this embodiment is an element that can form a FCC phase multi-principal alloy with good toughness with Fe, Co, and Cr elements, and the Y element in the CoCrNiZY multi-principal alloy is an alloy element that is easily nitrided and can promote the formation of Laves or BCC phases.
[0040] The multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitriding mechanism in this embodiment is composed of a CoCrNiX multi-principal alloy bottom layer, a CoCrNiZY multi-principal alloy top layer, and a CoCrNiZY multi-principal alloy nitrided layer. The CoCrNiX multi-principal alloy bottom layer is clad on the surface of the substrate by a high-energy beam cladding process, and then the CoCrNiZY multi-principal alloy top layer is continuously clad on the surface of the CoCrNiX multi-principal alloy bottom layer, and finally the CoCrNiX-CoCrNiZY gradient coating is ion nitrided, wherein X represents elements such as Ni and Cu that can form a FCC phase multi-principal alloy with good toughness with Fe, Co, and Cr elements; and Y represents refractory alloy elements such as W, Ta, Nb, Mo, Zr, and Hf.
[0041] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the base material described in step 1 is 38CrMoAl, 300M steel or A100 high-strength steel.
[0042] Specific embodiment three: This embodiment is different from specific embodiment one or two in that the particle size of Fe, Co, Cr, X, Y and Z metal powders in step two is 75-150 μm.
[0043] Specific implementation method four: This implementation method is different from any one of specific implementation methods one to three in that the grinding balls in the ball milling mixing process in step a or step b are Al2O3 ceramic balls, the ball-to-material mass ratio is controlled to be 3:1, the rotation speed is 250-300r / min, and the ball milling time is 30-50min.
[0044] Specific implementation mode 5: This implementation mode is different from any one of specific implementation modes 1 to 4 in that the high energy beam described in step 3 and step 4 is a laser beam or a plasma beam.
[0045] Specific implementation method six: The difference between this implementation method and specific implementation method five is that a laser beam cladding process is used in steps three and four, and the laser power is controlled to be 1000-2000W, the scanning rate is 10-25mm / s, the overlap rate is 25%-35%, the spot diameter is 3mm, and the powder feeding rate is 0.1-0.15g / s.
[0046] Specific implementation method 7: The difference between this implementation method and any one of specific implementation methods 1 to 6 is that the thickness of the CoCrNiX multi-principal alloy toughness bottom layer in step 3 is 0.3-0.7 mm.
[0047] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the nitriding time in step six is controlled to be 5 to 7 hours, the gas pressure to be 300 to 400 Pa, and the voltage to be 700 to 800 V during the ion nitriding treatment.
[0048] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 1 to 8 is that the thickness of the CoCrNiZY nitride layer in step 6 is 0.3-0.7 mm.
[0049] Specific embodiment ten: This embodiment is different from any one of specific embodiments one to nine in that the thickness of the multi-principal alloy coating with a multi-level heterogeneous structure obtained in step six is 1 to 1.5 mm.
[0050] Embodiment: The preparation method of the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism of this embodiment is implemented according to the following steps:
[0051] 1. Perform a pretreatment process on the 38CrMoAl high-strength steel matrix material, that is, perform grinding, polishing and cleaning in sequence to optimize the surface properties of the matrix;
[0052] 2. preparing CoCrNiFe multi-principal alloy powder and CoCrNiFeNb multi-principal alloy powder respectively;
[0053] a. The preparation method of the CoCrNiFe multi-principal alloy powder is as follows:
[0054] According to the atomic ratio of Fe:Co:Cr:Ni=1:1:1:1, four metal powders are accurately measured, and the powder particle size is 70~150μm. Then, these four metal powders are placed together in a high-energy ball mill. The grinding balls used in the ball mill are Al2O3, the ball-to-powder ratio is 3:1, the speed of the ball mill is 300r / min, and the ball milling time is 50min, so as to achieve deep and uniform mixing between the powders. After completing the mixing procedure, the powder is dried in a drying oven at 120℃ for 2h to obtain a CoCrNiFe multi-principal alloy powder with uniform composition.
[0055] b. The preparation method of the CoCrNiFeNb multi-principal alloy powder is as follows:
[0056] According to the atomic ratio of Fe:Co:Cr:Ni:Nb=1:1:1:1:1, the five metal powders are accurately weighed, and the powder particle size is 70-150μm. Subsequently, the five metal powders are placed together in a high-energy ball mill. The grinding balls used in the ball mill are Al2O3, the ball-to-powder ratio is 3:1, the speed of the ball mill is 300r / min, and the ball milling time is 50min, so as to achieve deep and uniform mixing between the powders. After completing the mixing procedure, the powder is dried at 120℃ in a drying oven for 2h to obtain a CoCrNiFeNb multi-principal alloy powder with uniform composition.
[0057] 3. The CoCrNiFe multi-principal alloy powder is fed synchronously to locally heat the surface of the pretreated matrix material by focusing the laser beam. The laser power is controlled to be 1500W, the scanning rate is 20mm / s, the overlap rate is 30%, the spot diameter is 3mm, and the powder feeding rate is 0.14g / s. A tough bottom layer of the CoCrNiFe multi-principal alloy is formed on the surface of the pretreated matrix material.
[0058] 4. The CoCrNiFeNb multi-principal alloy powder is fed synchronously, and the pretreated substrate surface is locally heated by focusing the laser beam. The laser power is controlled to be 1500W, the scanning rate is 20mm / s, the overlap rate is 30%, the spot diameter is 3mm, and the powder feeding rate is 0.14g / s. A CoCrNiFeNb multi-principal alloy top layer is formed on the CoCrNiFe tough bottom layer, and a gradient multi-principal alloy coating is formed by a gradient change in the content of the FCC phase and the hard phase (Laves phase or BCC phase) in the two multi-principal alloys.
[0059] 5. Grind and polish the surface of the gradient multi-principal alloy coating to remove minor defects on the coating surface, such as unevenness, residual particles or oxide layer;
[0060] 6. Place the substrate sample with the gradient multi-principal alloy coating into the cathode disk of the ion nitriding furnace, close the chamber, and cool it with the furnace after leakage inspection, ion etching, pressure increase, and insulation. Control the nitriding temperature to 600°C, the nitriding time to 6h, the gas pressure to 350Pa, and the voltage to 800V to obtain a multi-principal alloy coating with a multi-level heterogeneous structure.
[0061] The coating obtained in this embodiment is a multi-principal component alloy coating with a multi-level heterogeneous structure, which includes CoCrNiFe tough multi-principal component alloy-Laves phase-reinforced CoCrNiFeNb hard multi-principal component alloy-CoCrNiFeNb multi-principal component nitriding layer from the bottom layer to the top layer.
[0062] Comparative Example: The preparation method of the CoCrNiFeNb gradient multi-principal alloy coating of this embodiment is implemented according to the following steps:
[0063] 1. Perform a pretreatment process on the 38CrMoAl high-strength steel matrix material, namely grinding, polishing and cleaning, in order to optimize its surface properties;
[0064] 2. preparing CoCrNiFe multi-principal alloy powder and CoCrNiFeNb multi-principal alloy powder respectively;
[0065] a. The preparation method of the CoCrNiFe multi-principal alloy powder is as follows:
[0066] According to the specified atomic ratio of Fe:Co:Cr:Ni=1:1:1:1, the four metal powders are accurately measured, and the powder particle size is 70~150μm. Subsequently, the four metal powders are placed together in a high-energy ball mill. The grinding balls used in the ball mill are Al2O3, the ball-to-powder ratio is 3:1, the speed of the ball mill is 300r / min, and the ball milling time is 50min, so as to achieve deep and uniform mixing between the powders. After completing the mixing procedure, the powder is dried in a drying oven at 120℃ for 2h, and finally a CoCrNiFe multi-principal alloy powder with uniform composition is obtained;
[0067] b. The preparation method of the CoCrNiFeNb multi-principal alloy powder is as follows:
[0068] According to the specified atomic ratio of Fe:Co:Cr:Ni:Nb=1:1:1:1:1, the five metal powders are accurately weighed, and the powder particle size is 70-150μm. Subsequently, the five metal powders are placed together in a high-energy ball mill. The grinding balls used in the ball mill are Al2O3, the ball-to-powder ratio is 3:1, the speed of the ball mill is 300r / min, and the ball milling time is 50min, so as to achieve deep and uniform mixing between the powders. After completing the mixing procedure, the powder is dried at 120℃ in a drying oven for 2h, and finally a CoCrNiFeNb multi-principal alloy powder with uniform composition is obtained;
[0069] 3. The CoCrNiFe multi-principal alloy powder is fed synchronously to locally heat the surface of the pretreated matrix material by focusing the laser beam. The laser power is controlled to be 1500W, the scanning rate is 20mm / s, the overlap rate is 30%, the spot diameter is 3mm, and the powder feeding rate is 0.14g / s to form a CoCrNiFe tough bottom layer on the surface of the pretreated matrix material.
[0070] 4. The CoCrNiFeNb multi-principal alloy powder is fed synchronously, and the surface of the pretreated substrate material is locally heated by focusing the laser beam. The laser power is controlled to 1500W, the scanning rate is 20mm / s, the overlap rate is 30%, the spot diameter is 3mm, and the powder feeding rate is 0.14g / s to obtain a CoCrNiFeNb gradient multi-principal alloy coating.
[0071] The multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitridation mechanism obtained in this embodiment was subjected to an X-ray diffractometer to perform a microstructure test. The test results are as follows: Figure 2 As shown. With the help of PDF card calibration, it was found that the diffraction peak of NbN appeared at the position of Laves phase, and the diffraction peaks of FeN0.0499, CrN, Co5.47N, and Ni4N appeared at the position of FCC. The organization morphology was observed using a scanning electron microscope, and the results are shown in Figure 3As shown, it can be seen that after ion nitriding, the structure is still a two-phase structure, in which the large irregular phase is the Laves phase, and the lamellar stripe structure is the Laves phase and the FCC phase, and the structure is still a hypereutectic structure with the Laves phase as the main phase and the FCC phase as the auxiliary phase. According to the element distribution diagram, it can be seen that the N element has no obvious enrichment and is distributed more evenly, indicating that the nitrogen element has a good reaction with the elements in the FCC phase and the Laves phase. The friction performance of the embodiment and the comparative embodiment was tested using a friction and wear tester. The test results are shown in the figure. Figure 4 As shown in the figure. According to the experimental results, after nitrogen ion strengthening, the friction coefficient curve shows a downward trend, which shows that ion nitriding helps to improve the friction reduction performance of the coating. At the same time, according to the wear rate of the coating calculated based on the cross-section of the wear scar morphology, the wear rate of the comparative example is 0.998×10 -6 mm 3 / (N·m), the wear rate of the embodiment is 0.763×10 -6 mm 3 / (N·m), indicating that the multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitriding mechanism has better wear resistance, which is improved by 23.5% compared with before nitriding.
[0072] Table 1 Summary of performance of the embodiments of the present invention and comparative examples
[0073] Surface hardness (HV) Average friction coefficient <![CDATA[Wear rate (mm 3 / (N·m))]]> Example 1466.5 0.235 <![CDATA[0.763×10 -6 ]]> Comparative Example 773.7 0.269 <![CDATA[0.998×10 -6 ]]> .
Claims
1. A multi-principal alloy coating with a multi-level heterogeneous structure based on a co-reaction nitridation mechanism, characterized by The multi-principal alloy coating with a multi-level heterogeneous structure based on the co-reaction nitriding mechanism consists of a CoCrNiX multi-principal alloy tough bottom layer, a CoCrNiZY multi-principal alloy top layer and a CoCrNiZY nitrided layer. The CoCrNiX multi-principal alloy powder is used as the cladding powder, and a high-energy beam cladding process is adopted to form a CoCrNiX multi-principal alloy tough bottom layer on the surface of the substrate. Then, the CoCrNiZY multi-principal alloy powder is used as the cladding powder, and a high-energy beam cladding process is adopted to form a CoCrNiZY multi-principal alloy top layer on the CoCrNiX multi-principal alloy tough bottom layer. Finally, ion nitriding treatment is performed to form a CoCrNiZY nitrided layer. Among them, X in the CoCrNiX multi-principal alloy powder represents Fe or Cu, Z in the CoCrNiZY multi-principal alloy powder represents Fe or Cu, and Y represents Ti, W, Ta, Nb, Mo, Zr or Hf.
2. A method for preparing a multi-principal alloy coating with a multi-level heterogeneous structure based on a co-reaction nitridation mechanism, characterized in that The preparation method is achieved by the following steps:
1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material; 2. Prepare CoCrNiX multi-principal alloy powder and CoCrNiZY multi-principal alloy powder respectively; a. The preparation method of the CoCrNiX multi-principal alloy powder is as follows: The four metal powders of Co, Cr, Ni and X are placed in a ball mill for ball milling and mixing according to the atomic ratio of Co:Cr:Ni:X=1:1:1:m, and then dried to obtain CoCrNiX multi-principal alloy powder; b. The preparation method of the CoCrNiZY multi-principal alloy powder is as follows: According to the atomic ratio of Co:Cr:Ni:Z:Y=1:1:1:m:n, five kinds of metal powders, Co, Cr, Ni, Z and Y, are placed in a ball mill for ball milling and mixing, and after drying, CoCrNiZY multi-principal alloy powder is obtained; 3. Using CoCrNiX multi-principal alloy powder as cladding powder, the CoCrNiX multi-principal alloy powder is fed synchronously, and a high-energy beam cladding process is used to form a CoCrNiX multi-principal alloy toughness bottom layer on the surface of the pretreated substrate material; 4. CoCrNiZY multi-principal alloy powder is used as cladding powder. The CoCrNiZY multi-principal alloy powder uses a synchronous powder feeding method and adopts a high-energy beam cladding process to form a CoCrNiZY multi-principal alloy top layer on the CoCrNiX multi-principal alloy toughness bottom layer to obtain a base material with a gradient multi-principal alloy coating; 5. The top surface of the CoCrNiZY multi-principal alloy is then ground, polished and cleaned in sequence to obtain a base material with a gradient multi-principal alloy coating; 6. Put the substrate material with the gradient multi-principal alloy coating into the cathode disk of the ion nitriding furnace, introduce NH3, control the nitriding temperature at 500-600°C to perform ion nitriding treatment to form a CoCrNiZY nitriding layer, thereby obtaining a multi-principal alloy coating with a multi-level heterogeneous structure; In the CoCrNiX multi-principal alloy, X represents Fe or Cu, in the CoCrNiZY multi-principal alloy, Z represents Fe or Cu, Y represents W, Ta, Nb, Mo, Zr or Hf, m is 0.5 to 1.5, and n is 0.5 to 1.
5.
3. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that The matrix material described in step 1 is 38CrMoAl, 300M steel or A100 high-strength steel.
4. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that The grinding balls used in the ball milling and mixing process in step a or step b are Al2O3 ceramic balls, the ball-to-material mass ratio is controlled to be 3:1, the rotation speed is 250-300 r / min, and the ball milling time is 30-50 min.
5. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that The high energy beam described in step 3 and step 4 is a laser beam or a plasma beam.
6. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 5, characterized in that In step 3 and step 4, a laser beam cladding process is used, and the laser power is controlled to be 1000-2000W, the scanning rate is 10-25mm / s, the overlap rate is 25%-35%, the spot diameter is 3mm, and the powder feeding rate is 0.1-0.15g / s.
7. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that In step 3, the thickness of the tough bottom layer of the CoCrNiX multi-principal alloy is 0.3-0.7 mm.
8. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that In step six, during the ion nitriding treatment, the nitriding time is controlled to be 5 to 7 hours, the gas pressure to be 300 to 400 Pa, and the voltage to be 700 to 800 V.
9. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that In step six, the thickness of the CoCrNiZY nitride layer is 0.3-0.7 mm.
10. The method for preparing a multi-principal alloy coating having a multi-level heterogeneous structure based on a co-reaction nitridation mechanism according to claim 2, characterized in that The thickness of the multi-principal alloy coating with a multi-level heterogeneous structure obtained in step six is 1 to 1.5 mm.